ECTHR_COMMITTEE 39567/02_40281/02 vom 25. September 2012 , AFFAIRE PARENTI (HÉRITIER) ET DEIDDA c. ITALIE - Ecthr Committee (2012)
Violation de l'article 6 - Droit à un procès équitable (Article 6 - Procédure civile;Article 6-1 - Délai raisonnable); Violation: 6;6-1